PENGGUNAAN VIRTUAL REALITY PADA GAME CREED: RISE TO GLORY-CHAMPIONS EDITION - Tasya Chayrina, Awalia Rahmatia, Adek Kurniawan, Nabila Aprilioni, Vidya Nofriza, Chelsy Putri, Rini (CV. ADIBA AISHA AMIRA, 2024)
The use of Virtual Reality (VR) in the gaming industry has experienced rapid growth, providing immersive and immersive gaming experiences. This research explores the application of VR in the game